2004
DOI: 10.1055/s-2004-830861
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Substituted Indoles via Pd/C-Catalyzed Reaction in Water

Abstract: A general and one-pot synthesis of 2-alkyl/aryl substituted indoles via a tandem Pd/C mediated coupling/5-endo-dig cyclization of terminal alkynes (including acetylenic carbinols) with o-iodoanilides in water is reported. The reaction is carried out using PPh 3 and CuI as co-catalysts and 2-aminoethanol as a base. The reaction appears to tolerate a variety of functional groups present in the alkynes and does not require the use of any organic co-solvent.The indole nucleus is a frequently found unit in many nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…With the aim of developing a heterogeneous bimetallic catalysis in water, we took inspiration from the work of Pal et al [34], who reported the preparation of indoles in a Pd/C-catalysed reaction in water with CuI as co-catalyst, Ph 3 P as ligand and 2-aminoethanol as base. To our great pleasure, the application of these conditions with our Pd–Cu/C catalyst, for the coupling of iodoaniline 1 with phenylacetylene ( 2 ) provided the expected indole 3 with an excellent 90% yield (Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…With the aim of developing a heterogeneous bimetallic catalysis in water, we took inspiration from the work of Pal et al [34], who reported the preparation of indoles in a Pd/C-catalysed reaction in water with CuI as co-catalyst, Ph 3 P as ligand and 2-aminoethanol as base. To our great pleasure, the application of these conditions with our Pd–Cu/C catalyst, for the coupling of iodoaniline 1 with phenylacetylene ( 2 ) provided the expected indole 3 with an excellent 90% yield (Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…It is worthy to mention that while chloro group of 3-chloroquinoxalin-2-amines is known to participate in the Pd/C-Cu mediated alkynylation reaction , the chloro group of 4 remained inert in the present reaction perhaps due to the higher reactivity of iodo group of 5 towards the Pd catalyst. Thus, the active Pd(0) species generated in situ (Pal, 2009;Layek et al, 2009;Pal et al, 2004) (Scheme 2) undergoes oxidative addition with 5 rather than 4 to give the organo-Pd(II) species E-1 which on trans organometallation with copper acetylide generated in situ from CuI and 4 affords E-2. The reductive elimination of Pd(0) from E-2 affords the internal alkyne E-3 which subsequently undergoes Cu-mediated intramolecular ring closure to give the desired product 6 via E-4.…”
Section: Docking Studiesmentioning
confidence: 98%
“…In view of the promising in silico results obtained for B through docking studies we planned to synthesize molecules based on A including B. A Pd/C-catalyzed coupling-cyclization strategy leading to the formation of indole ring was used to prepare our target molecules (Scheme 1) (Pal 2009;Layek et al, 2009' Pal et al, 2004. We preferred this strategy as the concerned methodology involved the use of less expensive, stable, easy to handle and recyclable Pd/C which is advantageous over the other Pd-based methodologies.…”
Section: Docking Studiesmentioning
confidence: 99%
“…The reaction of N-acyl 2-iodoaniline with alkyl, aryl, and heteroaryl substituted terminal alkynes using various reaction conditions like changing the concentration of base/additive/Pd-zeolite, solvent and temperature to get higher yields of the 2-substituted indoles (140) along with open chain compounds (141) was studied by Hong et al [112]. The optimal reaction condition for the higher yields was 5 mol % of Pdloaded zeolite, 1 equiv LiCl, 2 equiv Cs 2 CO 3 and DMF at 140 o C. Pal et al [111] have described a one-pot synthesis of 2-alkyl/arylsubstitued indoles (138) Botta and co-workers [113,114] reported the stereoselective synthesis of α-aryl-1H-indole-2-methanamines (144) by reacting racemic and enantiomerically pure arylpropargylamines (142) with o-halo aniline derivative via palladium and copper catalyzed heteroannulation. Yamanaka and co-workers [115] succeeded in synthesizing indoles (146) from terminal alkynes and N-(2-iodophenyl)methane sulfonamide (145) by employing a palladium and copper bimetallic catalyst.…”
Section: Bimetalic Catalysis In the Sonogashira Cross-coupling Reactionmentioning
confidence: 97%